2013
DOI: 10.1111/his.12099
|View full text |Cite
|
Sign up to set email alerts
|

Expression of olfactomedin 4 and claudin‐18 in serrated neoplasia of the colorectum: a characteristic pattern is associated with sessile serrated lesion

Abstract: Reduced expression of olfactomedin 4 and ectopic expression of claudin-18 might be useful markers in the differential diagnosis of serrated polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
2
20
0
1
Order By: Relevance
“…In CLDN18-expressing cases, the pathology of colon cancer is similar to that of gastric cancers, and CLDN18 expression is related to poor survival [74]. CLDN18 expression has also been reported to be associated with serrated adenocarcinoma of the colon [75]. These data indicate that aberrant expression of TJ proteins and of phenotype markers is strongly related to the progression and poor prognosis of cancers.…”
Section: Colon Cancermentioning
confidence: 91%
“…In CLDN18-expressing cases, the pathology of colon cancer is similar to that of gastric cancers, and CLDN18 expression is related to poor survival [74]. CLDN18 expression has also been reported to be associated with serrated adenocarcinoma of the colon [75]. These data indicate that aberrant expression of TJ proteins and of phenotype markers is strongly related to the progression and poor prognosis of cancers.…”
Section: Colon Cancermentioning
confidence: 91%
“…It was reported that the activation of Wnt/β‐catenin signaling occurred via distinct mechanisms in both pathways . Furthermore, there are several immunohistochemical markers that can assist in the conventional morphological diagnosis in tumors that develop via the colorectal carcinogenesis pathway, including, but not limited to p53, β‐catenin, claudin‐18, MLH1 and MSH2 . In the present study, we analyzed the significance of SPC18 in pre‐cancerous lesions of both colorectal carcinogenesis pathways.…”
mentioning
confidence: 95%
“…In the search for new therapeutic or diagnostic markers, it is generally accepted that genes expressed at high levels in tumors and at very low levels in normal tissues are ideal diagnostic or therapeutic molecules . We previously reported that Reg IV, olfactomedin 4, claudin‐18 and h‐prune are prognostic makers for CRC . In the present study, we searched for the candidate genes that met these conditions in our comprehensive gene expression libraries, and focused on SEC11A , which encodes the SPC18 protein .…”
mentioning
confidence: 99%
“…CLDN1 was found to be upregulated in polyps bearing the BRAF V600E somatic mutation, on both the gene expression and protein level . Another study that investigated immunohistochemical detection of CLDN18 in serrated pathway lesions found higher expression of this TJ protein in sessile‐serrated adenomas than in hyperplastic polyps or conventional adenomas . Furthermore, mucin‐5AC expression was reported to be higher in sessile‐serrated adenomas than in normal colon tissue and hyperplastic polyps .…”
Section: Discussionmentioning
confidence: 99%
“…53 Another study that investigated immunohistochemical detection of CLDN18 in serrated pathway lesions found higher expression of this TJ protein in sessile-serrated adenomas than in hyperplastic polyps or conventional adenomas. 54 Furthermore, mucin-5AC expression was reported to be higher in sessile-serrated adenomas than in normal colon tissue and hyperplastic polyps. 55 Mucin "positive" colorectal carcinomas (where staining was observed in more than 25% tumor cells for mucin-2 or >0% for mucins-5AC and -6) were more likely to be CIMP-positive and BRAF V600E-mutated relative to colorectal carcinomas that did not meet the staining threshold.…”
Section: Discussionmentioning
confidence: 99%